2007
DOI: 10.1038/sj.emboj.7601675
|View full text |Cite
|
Sign up to set email alerts
|

Cdk6 blocks myeloid differentiation by interfering with Runx1 DNA binding and Runx1-C/EBPα interaction

Abstract: Interactions between the cell cycle machinery and transcription factors play a central role in coordinating terminal differentiation and proliferation arrest. We here show that cyclin-dependent kinase 6 (Cdk6) is specifically expressed in proliferating hematopoietic progenitor cells, and that Cdk6 inhibits transcriptional activation by Runx1, but not C/EBPalpha or PU.1. Cdk6 inhibits Runx1 activity by binding to the runt domain of Runx1, interfering with Runx1 DNA binding and Runx1-C/EBPalpha interaction. Cdk6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
86
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 29 publications
2
86
0
Order By: Relevance
“…Moreover, there is mounting evidence for a specific role for Cdk6 in differentiation, especially in neuronal and haematopoietic cells (Ericson et al, 2003;Slomiany et al, 2006;Fujimoto et al, 2007;Grossel and Hinds, 2006;Matushansky et al, 2003). These studies support the idea that the G1 Cdks have overlapping, yet distinct, activities.…”
supporting
confidence: 73%
“…Moreover, there is mounting evidence for a specific role for Cdk6 in differentiation, especially in neuronal and haematopoietic cells (Ericson et al, 2003;Slomiany et al, 2006;Fujimoto et al, 2007;Grossel and Hinds, 2006;Matushansky et al, 2003). These studies support the idea that the G1 Cdks have overlapping, yet distinct, activities.…”
supporting
confidence: 73%
“…How cell cycle regulatory proteins like Fbxo7 and Cdk6 influence differentiation and cell cycle, and at which maturation stage this occurs is an interesting question for future study. There are experimental data that indicate direct binding of Cdk6 to transcription factors that regulate differentiation, suggesting a cellcycle-independent function (Fujimoto et al, 2007), whereas other studies show that downregulation of Cdk6 protein is crucial for terminal differentiation, presumably by allowing a permanent withdrawal from the cell cycle (Matushansky et al, 2003). In addition, it is possible that these proteins have different regulatory roles, cell cycle and/or transcriptional functions at different times in cell maturation.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed it has been reported that CDK6 blocks the myeloid differentiation by inhibiting the activity of AML-1. 45 In addition, CDK6 expression decreases during erythroid differentiation independently of the cell cycle. 31 Thus, if a similar down-regulation of CDK6 occurs during megakaryopoiesis, it will be associated with an increase in AML-1 activity leading both to a cell-cycle arrest and MK differentiation.…”
Section: Discussionmentioning
confidence: 99%